The reliability and process capability assessment of suspended growth sewage treatment plant in Melaka, Malaysia - A. Ishak; E. Mohamad; A. Hambali; N. L. Johari (Water Science and Technology, 2022)
This paper presents the promising method of synchronizing the Six Sigma and reliability analyses at 15 sewage treatment plants (STPs) operating in Melaka, Malaysia. Five different suspended growth treatment technologies in various capacities were investigated. The sequential batch reactor (SBR) and extended aeration activated sludge (EAAS) processes, conventional activated sludge (CAS), aerated lagoon (AL), and oxidation pond (OP) were compared using innovative Niku's treatment reliability and Six Sigma process capability method for biological oxygen demand (BOD5), chemical oxygen demand (COD), total suspended solids (TSS), oil and grease (O&G), and ammoniacal nitrogen (NH3-N) effluent parameters and justified the importance of understanding the lognormal behavior of the effluent parameters in interpreting the performance monitoring results and discharge compliance. The results showed that the SBR and EAAS systems relatively fulfilled the highest performance (>95%) compared to conventional systems to ensure the high quality of effluent discharge. Although the whole system is incapable of removing nutrients efficiently, ranging between 42.31% and 90.48%, may lead to eutrophication issues. Process modification and treatment control should become a critical priority in order to reduce variability, improve stability, and increase the efficiency of nutrient removal. These initiatives promote global sustainable development goals (SDGs) 2030 and the domestic water sector transformation (WST) 2040 by treatment cost reduction, improving environmental sustainability and guaranteeing social and health benefits. HIGHLIGHTS Performance monitoring of suspended growth sewage treatment systems was investigated.; Niku's probabilistic reliability analysis and Six Sigma process capability indices were synergized.; Nutrient removal efficiency from 42.31% to 90.48%.; Highly mechanical systems perform better with treatment reliability.; Proper planning for Malaysia to revamp the wastewater industry according to SDGs and domestic WST 2040 targets.;